Investigating the evolution and development of biological complexity under the framework of epigenetics. Issue 5 (3rd July 2019) - Duclos, Kevin K.; Hendrikse, Jesse L.; Jamniczky, Heather A.
Abstract : Biological complexity is a key component of evolvability, yet its study has been hampered by a focus on evolutionary trends of complexification and inconsistent definitions. Here, we demonstrate the utility of bringing complexity into the framework of epigenetics to better investigate its utility as a concept in evolutionary biology. We first analyze the existing metrics of complexity and explore the link between complexity and adaptation. Although recently developed metrics allow for a unified framework, they omit developmental mechanisms. We argue that a better approach to the empirical study of complexity and its evolution includes developmental mechanisms. We then consider epigenetic mechanisms and their role in shaping developmental and evolutionary trajectories, as well as the development and organization of complexity. We argue that epigenetics itself could have emerged from complexity because of a need to self‐regulate. Finally, we explore hybridization complexes and hybrid organisms as potential models for studying the association between epigenetics and complexity. Our goal is not to explain trends in biological complexity but to help develop and elucidate novel questions in the investigation of biological complexity and its evolution. Abstract : Biological complexity is the result of the hierarchical organisation of nested levels of cells, tissues and higher order part types interacting together. RESEARCH HIGHLIGHTS: This manuscript argues that biological complexity is better understood under the framework of epigenetics and that the epigenetic interactions emerge from the self‐regulation of complex systems. Hybrids are offered as models to study these properties.